2016
DOI: 10.3390/ma9110886
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Glass Fiber Reinforced Composites Based on Bio-Oil Phenol Formaldehyde Resin

Abstract: In this study, bio-oil from fast pyrolysis of renewable biomass was added by the mass of phenol to synthesize bio-oil phenol formaldehyde (BPF) resins, which were used to fabricate glass fiber (GF) reinforced BPF resin (GF/BPF) composites. The properties of the BPF resin and the GF/BPF composites prepared were tested. The functional groups and thermal property of BPF resin were thoroughly investigated by Fourier transform infrared (FTIR) spectra and dynamic thermomechanical analysis (DMA). Results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The water in the samples would be physically adsorbed from the air before the FTIR measurements after calcination. Compared with curve a in the infrared spectrum, curve b has peaks of 1086, 1466, 2852, and 2922 cm −1 more than the curve a, corresponding to the stretching vibrations of the Si–O–Si bond, the deformation vibrations of the –NH 2 , and the symmetric and anti-symmetric stretching of the –CH 2 –, respectively [8,30]. Therefore, the presence of these groups on the surface of the modified glass fiber indicates that KH-550 was successfully coupled to the surface of the glass fiber [31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The water in the samples would be physically adsorbed from the air before the FTIR measurements after calcination. Compared with curve a in the infrared spectrum, curve b has peaks of 1086, 1466, 2852, and 2922 cm −1 more than the curve a, corresponding to the stretching vibrations of the Si–O–Si bond, the deformation vibrations of the –NH 2 , and the symmetric and anti-symmetric stretching of the –CH 2 –, respectively [8,30]. Therefore, the presence of these groups on the surface of the modified glass fiber indicates that KH-550 was successfully coupled to the surface of the glass fiber [31].…”
Section: Resultsmentioning
confidence: 99%
“…The curing of these combined materials provides excellent electrical insulation, thermal stability, flame retardancy, and heat resistance properties [2,3,4,5]. Glass fiber (GF)-reinforced phenol formaldehyde resin-based composites have been widely applied in radar radome, automobile fittings, printed circuit board, and so on by virtue of their light weight, high specific strength, and excellent electrical and thermal insulation properties [6,7,8]. The reinforcing effect of glass in phenol formaldehyde resin has been evaluated at various glass fiber loadings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic viscosity of HPFA reached 112 mPa·s, which results from the increase of solid content and molecular weight in the polycondensation reaction. The cured HPFA has a smoother and more compact structure compared to the cured ADH as shown in Figure 1 B,C, indicating that the polycondensation reaction improves the crosslink density among the constituents of HPFA [ 28 ]. This was also shown by the C 13 NMR analysis shown in Figure 3 B, since the peaks at 129 and 150 ppm of cured HPFA were sharper than that of cured ADH [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cui and co-workers reported that the BPF resins have similar FT-IR spectra as PF resin. This indicates that the BPF resins display a similar molecular structure as the PF resin (Cui et al, 2016). According to FT-IR analysis, it can be claimed that bio-based resol resins were successfully produced by polymerization of phenol, bio-oil and formaldehyde.…”
Section: Characterization Of Resins 32 Karakterizacija Smolamentioning
confidence: 81%